Evaluating SARS-CoV-2 spike and nucleocapsid proteins as targets for antibody detection in severe and mild COVID-19 cases using a Luminex bead-based assay - Mariën, Joachim; Ceulemans, Ann; Michiels, Johan; Heyndrickx, Leo; Kerkhof, Karen; Foque, Nikki; Widdowson, Marc-Alain; Mortgat, Laure; Duysburgh, Els; Desombere, Isabelle; Jansens, Hilde; Van Esbroeck, Marjan; et al. (Journal of virological methods, 2021)
•We evaluated a bead-based Luminex assay for the detection of SARS-CoV-2 antibodies.•A combination of the nucleocapsid protein and the receptor-binding domain results in a highly sensitive (96 %) and specific (99 %) assay that can detect positive cases at least five months after infection.•Because we find that IgG and neutralizing antibody levels can differ significantly between severe/mild and recent/old cases, we argue that serological tests should be validated on samples from all groups before use in serosurveillance studies. Large-scale serosurveillance of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) will only be possible if serological tests are sufficiently reliable, rapid and affordable. Many assays are either labour-intensive and require specialised facilities (e.g. virus neutralization assays), or are expensive with suboptimal specificity (e.g. commercial ELISAs and RDTs). Bead-based assays offer a cost-effective alternative and allow for multiplexing to test for antibodies against multiple antigens and against other pathogens. Here, we compare the performance of spike (S) and nucleocapsid (NP) antigens for the detection of SARS-CoV-2 specific IgG, IgM and IgA antibodies in a panel of sera that includes recent (up to six weeks after symptom onset, severe n = 44; and mild cases n = 52) and old infections (five months after symptom onset, mild n = 104), using a Luminex-bead based assay and comparison to a virus neutralization test. While we show that neutralizing antibody levels are significantly lower in mild than in severe cases, we demonstrate that a combination of the recombinant nucleocapsid protein (NP) and receptor-binding domain (RBD) results in highly specific (99 %) IgG antibody detection five months after infection in 96 % of cases. Although most severe Covid-19 cases developed a clear IgM and IgA response, titers fell below the detection threshold in more than 20 % of mild cases in our bead-based assay. In conclusion, our data supports the use of RBD and NP for the development of SARS-CoV-2 serological IgG bead-based assays.